Analisis Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja Karyawan Pada PT Sumi Asih Bekasi (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
The company's ability to grow is inseparable from the great help and support of employees. Employees are the most important asset and must be maintained, because employees are a benchmark for the progress of the company, every company always wants employees to work optimally, but sometimes companies forget that employees also want appropriate and fair rewards for their work. The problem in this study is whether leadership affects employee performance, does motivation affect employee performance, whether leadership and motivation together can affect employee performance. This type of research is quantitative. Data collection techniques in this study are primary data collected by researchers directly in the field. For data analysis using statistical tests and calculations using multiple linear regression analysis. Based on the calculation of multiple linear regression analysis, the results are Y = 3,312 + 0.825 X1 + 0.096 X2. And R Square of 0.829 means that the contribution of leadership and motivation to employee performance is 82.9% while the remaining 0.171 or 17.1% is influenced by other factors. Partially, leadership has a positive and significant effect on employee performance as indicated by a significance level of 0.000 <0.05 and motivation does not have a significant effect on employee performance as indicated by a significance level of 0.292> 0.05. And simultaneously it shows that the variables of leadership and motivation have a positive and significant effect on employee performance as indicated by the significance level of 0.000 <0.05.